Grouping of Meroplankton Habitat in Jakarta Bay and Seribu Island - Reny Puspasari; Aisyah, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Jakarta Bay is an estuarine ecosystem and facing the small island groups of Seribu Island. Jakarta Bay is known as nursery ground for many marine biotas, determined by numerous numbers of meroplankton. The distributions of meroplankton are highly influence by environmental conditions of Jakarta Bay and Seribu Islands. This research objective was to analyze the habitat preferences of some meroplankton groups such as shrimp, mollusk, crab and fish larvae in Jakarta Bay and Southern Seribu Islands. Fish larvae sampling was conducted in 13 stations that categorized into estuarine and small island stations in Jakarta Bay and Southern Seribu Island, combination of seven estuarine stations and six small island stations. The results found that there was a variation on the distribution and composition of meroplankton in sampling area. There were six groups of marine meroplankton, namely shrimps, mollusk, crabs, fish, jelly fish and squid larvae in Jakarta Bay and Seribu Island. The abundance of shrimp, mollusk and fish larvae is higher in April than August. The abundance of crab larvae is higher in August than April, while the others are found in small number both in April and August. Shrimps, fish and mollusks larvae have no specific preferences in habitat used, however they mostly used small island stations as their habitat compare to estuary, which has high temperature and salinity